Effects and formula optimization of Rosa roxbunghii pomace substrate on the yield and volatile flavor compounds of Lentinulaedodes - Deng, Tingfei; Li, Liangqun; Li, Chunyan; Yan, Yanfang; Gao, Anqin; Liu, Xiaolan; Pan, Xiong; Gao, Ming; Ge, Lijuan; Peng, Mei; Luo, Zhongsheng; Tian, Yan; et al. (Frontiers in Plant Science, 2025)
IntroductionRosa roxbunghii pomace (RRP), a by-product of R. roxbunghii processing, remains largely underutilized. Given the increasing demand for sustainable and resource-efficient mushroom cultivation methods, exploring RRP as a mushroom cultivation medium could not only address waste management issues but also potentially enhance the quality of cultivated mushrooms. This study aimed to investigate the effects of RRP at different proportions on the yield and volatile flavor compounds of Lentinula edodes, and to optimize the formula of the cultivation substrate.MethodsDifferent proportions of RRP were incorporated into the cultivation substrate of Lentinula edodes to form various test formulas. The mushroom yield of each formula was measured by counting the harvested weight per cultivation bag. Advanced gas chromatography-mass spectrometry (GC-MS) was employed to analyze the volatile flavor profiles of the mushrooms cultivated under different formulas. Principal component analysis (PCA) was conducted to explore the differences in volatile flavor substances among formulas and compared with the control group.ResultsAmong the tested formulas, a mixture containing 30% RRP (Formula 2) showed the highest yield, reaching 0.85 kg per cultivation bag, significantly outperforming other formulas. GC-MS analysis revealed distinct volatile flavor profiles for each formula. Formula 2 was characterized by its unique flavor attributes, with 1-octen-3-ol accounting for 29.16% of the relative content, a key compound contributing to the umami flavor of mushrooms. PCA results further confirmed that the volatile flavor substances of Formula 2 were significantly different from those of the control group.DiscussionThese findings demonstrate that incorporating RRP into mushroom cultivation substrates can enhance both yield and flavor characteristics of L. edodes. The optimal formulation (30% RRP) not only supported maximum productivity but also contributed to a more desirable aroma profile. This study presents an innovative and sustainable approach to repurposing agricultural waste, adding value to both mushroom production and resource utilization.